Del Imperio a la Colonia: Transformaciones y Conflictos en el Brasil Portugués del Siglo XVIII - Costa, Daniel (2025)
Reseña de: SCHULTZ, Kirsten. From Conquest to Colony: Empire, Wealth, and Difference in Eighteenth-Century Brazil. New Haven: Yale University Press, 2023.